A Development of a Training Module on Restorative Justice to Promote Teachers’ Servant Leadership - Dwioktorianto Effendy, Samuel; Wibawanta, Budi (Lembaga Layanan Pendidikan Tinggi Wilayah III DKI Jakarta, 2023)
The enactment of restorative justice is vital in schools to foster a caring community and so shape students' characters. Effective implementation requires teachers to act as servant leaders. However, the authors observe a lack of information and skills in this area. Therefore, this study aims to develop a training module on restorative justice to promote teachers’ servant leadership by ADDIE (Analysis, Design, Development, Implementation, and Evaluation) instructional model. The scope of this research is until the Development phase of the ADDIE process that includes producing the training module and evaluating its effectiveness in a pilot test. The training module consists of 5 sections covering 6 instructional goals. The module is designed as a fully asynchronous online training. Based on the results of pilot training, the training module substantially closes the performance gap of the learners. The training module is ready to be used in a training program for teachers.